Optimization of ultrashort pulse laser in ring-type erbium-doped fiber laser with single wall carbon nanotube saturable absorber - Mohamad, Hafizah (2016)
Research works based on pulsed mode-locked fiber laser (MLFL) were realized by employing numerous techniques such as nonlinear polarization rotation, saturable absorber (SA) and active modulator. The generation of MLFL encourages substantial research efforts due to its fascinating characteristics such as ultrashort pulse duration, broad spectral bandwidth and intense pulse energy, which are highly desirable in various industrial applications. The MLFL possesses several significant issues that need to be addressed such as dispersion management and operating wavelength region. Subsequently, this research work focuses on both issues, which are dispersion optimization and switchable wavelength laser operation In this research, a ring-configuration erbium-doped fiber laser (EDFL) setup is employed to generate multiwavelength-based MLFL which is assisted by an inline single-walled carbon nanotube (SWCNT) SA. The ultrashort pulse signal initiated by this SA is accompanied with the typical soliton-based mode-locked laser characteristics such as the observation of multiple Kelly’s sidebands, output pulse train with constant round-trip time, and pulse width within femtosecond range. The initial work in this experiment is to investigate dispersion management within the mode-locked EDFL, leading to pulse width generation of 970 fs with the employment of 10 m HP980 erbium-doped fiber (EDF). This MLFL regime generates multiple pulses which resembles the harmonic mode-locking laser scheme. This pulsed laser scheme is unstable, due to the lengthy EDF used which contributes to high nonlinear effects at high pump power. Therefore, the EDF length is shortened to 5 m in order to reduce the possibility of unstable pulses generation as aforementioned. The pulse width generated by 5 m EDF-incorporated MLFL is 886 fs, with more stable pulses observed from spectral and temporal measurements. Dual-laser regime is observed with the lasers observed at around 1530 nm and 1560 nm. Therefore, a red/blue coupler is employed in order to provide a cleaner output at 1560 nm. After the laser cavity is optimized through length variation of single mode fiber, the pulse width is found at 864 fs with total cavity length of 17m. Based on the experimental findings during dispersion management process, the dual-laser regime is employed in order to generate switchable dual-lasing MLFL. The mode-locked laser output can be discretely varied from 1533 nm to 1560 nm or can be made to simultaneously oscillate at both regions, thus producing a dual-wavelength mode-locked operation. This is realized by spooling the fiber in the laser cavity into different radii of 1.60 cm, 1.07 cm and 0.80 cm respectively, resulting in the respective insertion loss of 0.11 dB, 1.21 dB and 4.20 dB. Subsequently, the pulse widths generated by each case are 734 fs, 800 fs and 1.06 ps, respectively. Therefore, by spooling the fiber into different radii, the switchable MLFL is generated at different wavelength region, where the pulse width can be tailored. In conclusion, this research work has successfully overcome the issues in MLFL performance on dispersion management and operating wavelength bands. Both issues are significant in typical MLFL where further research investigation can be made in studying the different mode-locked regimes of dark pulse, stretch pulse and harmonic pulse.